Current research in bilingualism and its implications for Cognitive Translation and Interpreting Studies - Schwieter, John W.; Festman, Julia; Ferreira, Aline (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This article discusses research in the field of bilingualism that has the potential to inform the related, albeit disconnected, field of Cognitive Translation and Interpreting Studies (CTIS). It reviews issues such as lexical access and the multilingual mental lexicon, inhibitory control and the “bilingual advantage debate”. This debate refers to the question whether bilingualism leads to cognitive advantages that monolinguals do not develop. Although these claims have not been fully tested in translators and interpreters – both novice and advanced professionals – it is plausible that if there are indeed cognitive advantages that arise from managing “two languages in one mind”, such benefits may correlate with neural and cognitive changes due to the training, accumulated experience and expertise of translators and interpreters. These topics merit inclusion in the expanding set of prominent research themes in CTIS. Future research in CTIS can use findings from bilingualism and the bilingual advantage debate to account for the peculiarities of translational cognition.